2003
DOI: 10.1046/j.1365-3148.2003.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a new enzyme‐linked immunosorbent assay for detection of total hepatitis C virus core antigen in blood donors

Abstract: Recent studies have shown that total hepatitis C virus (HCV) core antigen, both free and antibody bound, is an accurate indirect marker of viral replication that can be used in clinical practice. The aim of the present study was to evaluate the performance of a new total HCV core antigen enzyme-linked immunosorbent assay (ELISA) for detection and quantification of total core antigen in blood donors, testing positive for anti-HCV antibodies and for prospective low-risk population screening. A population compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…HCV core antigen was detected in the vast majority (94.7%) of specimens containing HCV-RNA. Our results are not surprising considering previous findings [Cano et al, 2003;Laperche et al, 2003;Lunel et al, 2003]. The limit of detection of the trak-C assay in IU/mL of HCV-RNA using the WHO 96/ 793 standard has been reported to be approximately 10,000 .…”
Section: Discussionsupporting
confidence: 83%
“…HCV core antigen was detected in the vast majority (94.7%) of specimens containing HCV-RNA. Our results are not surprising considering previous findings [Cano et al, 2003;Laperche et al, 2003;Lunel et al, 2003]. The limit of detection of the trak-C assay in IU/mL of HCV-RNA using the WHO 96/ 793 standard has been reported to be approximately 10,000 .…”
Section: Discussionsupporting
confidence: 83%
“…To the best of our knowledge, five studies evaluated the usefulness of HCV core antigen as a marker of active/ongoing HCV infection in the therapynaïve patients [Cano et al, 2003;Agha et al, 2004;Krajden et al, 2004;Netski et al, 2004;Valcavi et al, 2004]. These studies reported on HCV RNA positive samples from 114 to 348 and showed the OTCA to be 86.9-97.4% as sensitive as NAT.…”
Section: Discussionmentioning
confidence: 99%
“…surement of HCV RNA viral load (2,12,20). This test has also been shown to be appropriate for screening for HCV infection in blood donors (3). The ability of this assay to identify viremic subjects in the general population has never been evaluated prospectively.…”
Section: Discussionmentioning
confidence: 99%